Samarium hexaboride is a trivial surface conductor - P. Hlawenka (Nature Portfolio, 2018)
Samarium hexahoride is argued to be a topological Kondo insulator, but this claim remains under debate. Here, Hlawenka et al. provide a topologically trivial explanation for the conducting states at the (100) surface of samarium hexaboride; an explanation based on Rashba splitting and a surface shift of the Kondo resonance.